Roman Jakobson's Semiotic Theory in revealing the Function of the Prophet's Communication Language - Frida Anggraini; Dayudin Dayudin; Yadi Mardiansyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Language is a tool of communication to convey understanding between the sender and the receiver of the message. Semiotic communication according to Roman Jakobson emphasizes the relationship between sign, meaning, and context. This research analyzes the function of language in the communication of the Prophet Muhammad SAW in the book Khulashoh Nurul Yaqin using Roman Jakobson's semiotic theory. This research uses a descriptive approach aimed at describing and interpreting phenomena through descriptive narratives in the analysis of language functions through speech. Using library research and note-taking methods as data collection techniques. The main focus of the research is the six functions of language, namely referential, emotive, poetic, phatic, conative, and metalingual. And the actions of the Prophet Muhammad SAW in various conditions when preaching. This research concludes that the communication of the Prophet Muhammad SAW, both verbal and non-verbal, encompasses referential, emotive, poetic, phatic, conative, and metalingual functions. His actions emphasized justice, honor, and exemplary conduct, teaching discipline, compassion, and unity. The Prophet Muhammad's SAW teachings through words and concrete actions built a civilized and compassionate society, becoming an eternal example for the community